Understanding temporality and future orientation for young women in the senior year. Issue 6 (2nd November 2017) - Duggan, Shane
ABSTRACT: This article considers how time is imagined, lived, and desired in young women's lives as they undertake their final year of secondary school studies in Melbourne, Australia. It argues that economic and competitive imperatives have intensified for many young people in recent times, manifesting in an educational apparatus that increasingly defines the parameters of success and achievement in terms of self-regulation and personal responsibility, and that this is particularly pronounced for young people as they prepare for, and aspire towards tertiary pathways. This article draws upon interviews and a-synchronous 'blog' posts from two young women who participated in a year-long study of young people enrolled in their final year of secondary school studies. It suggests that the intensification, compression, and control of time in educational discourse around the senior year plays a powerful role in self-making for young women in particular.